EMOTIONAL NEEDS ASSESSMENT OF ATTRIBUTES OF ALTERNATIVE POWER GENERATOR TO KUALA DISTRICT COMMUNITIES - ROSNANI GINTING; Juliza Hidayati; Muhammad Zulfin; Alfin Fauzi Malik (Jurnal Ilmiah Teknik Industri, 2020)
The purpose of this study to identify the technical needs and requirements of in Langkat District related to the power generation design variables, outlined in the form of a functional and non-functioning questionnaires. The power plant product attributes based on the results of the kano questionnaire distribution revealed that the price attribute and durability of the generator was in the attractive category. while the attributes of ease of operation are included in the one dimensional category. while aesthetics is the only attribute that falls into the indifferent category